Interlaboratory agreement in assessment of gynaecological cytology in Cervical Cancer Screening Programme in Poland – a pilot evaluation - Zalewska-Otwinowska, Kinga; Macios, Anna; Komerska, Katarzyna; Rekosz, Małgorzata; Nowakowski, Andrzej (Polish Journal of Pathology, 2021)
In our pilot study we have aimed to assess interlaboratory variability of cytological diagnoses in selected laboratories participating in the Polish Cervical Cancer Screening Programme (CCSP) to establish grounds for certification system for cytodiagnosticians and to monitor the quality of services. Set of 50 selected Pap smears, previously reassessed by an expert on the grounds of clinical, colposcopic and histological data was blinded and sent to 15 laboratories in Poland with request for evaluation according to routine practice according to the Bethesda 2001 system. Concordance with expert diagnoses reached a median of 82% (range: 66% to 92%), with median unweighted κ coefficient at κ = 0.67 (range 0.40 to 0.86) depending on laboratory. This indicates substantial agreement among laboratories, however with essential differences in proper evaluation in some outlying laboratories. Agreement was highest in samples with high-grade, lower for low-grade abnormalities. Slides with ASC-US and ASC-H expert diagnoses were most troubling for cytodiagnosticians. Sets of highly selected cytological slides with expert diagnoses may serve as a tool in the process of comprehensive periodic recertification of cytodiagnosticians in the screening programme. A benchmark level of agreement with expert diagnoses should be established to guide corrective actions for cytodiagnosticians with lowest agreement.